Muslim women's role in reproductive health decision making and their vulnerability to STIs and HIV & AIDS in Ankpa LGA of Kogi State Nigeria - Idris, Hussayn Umar (2017)
The United Nations (UN) named year 2000 as the year in which gender equality, development and peace shall be guaranteed women for the twenty first century. The UN emphasized that gendered issues surrounding the reproductive life of women be paid serious consideration in promoting the Reproductive Health Decision-Making (RDHM) process. This study explored spousal communication between couples in Ankpa LGA where gender dictates the life of people. The presenting problem also implied how vulnerable married women were to Sexually Transmitted Infections (STIs) and Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) due to their lack of contribution to RHDM. The studies objectives were to: (a) analyze women’s role in the RHDM process; (b) explain the key factors influencing women’s participation in RHDM; (c) determine the impacts of women’s involvement in RDHM; (d) analyze the challenges faced by women in contributing to the RHDM and; (e) develop a communication model that facilitates participation RHDM. Through a qualitative research purposive sampling was employed to select twenty married women as informants and two focus group discussions (FGDs). The in-depth interviews were used for data collection. Findings were analyzed using thematic content analysis and showed that objective (1) the analysis of women’s role RHDM showed lack of knowledge of RH and reproductive rights, (2) the key factors impeding women’s participation in RHDM were explained in the findings of the study (3) for the third objective it was also agreed that married women do not contribute to RHDM due to the challenges faces as shown in the second objective and (4), and finally the fourth objective showed that women are vulnerable to STIs and HIV&AIDS, and finally (5) the study was able to design a communication model that can enhance women’s communication ability and facilitate participation on RHDM.